Composition and Abundance of Phytoplankton with Potential Harmful Algal Blooms (HABs) on Ternate Island Coastal Waters, North Maluku - Ramili, Yunita; Umasangaji, Halikuddin; Drakel, Andreyan (Agrikan Jurnal Agribisnis Perikanan, 2023)
The existence of several species of phytoplankton with potential HABs (Harmful Algal Blooms) was investigated on the coastal waters of Ternate Island. This work aims at describing the distribution, species composition, and the abundance of phytoplankton with potential HABs and their ecological index. Data collection was carried out in August 2022 in the coastal waters of Ternate Island at three research locations, namely in Dorpedu (Station 1), Falajawa, Muhajirin Village (Station 2) and Kulaba (Station 3), respectively. Sampling of phytoplankton uses a filtering method with a plankton net. The results of this study quantified 24 genera of phytoplankton where 11 generas were included the group of potential HABs, namely Leptocylindrus, Coscinodiscus, Pseudo Nitzschia. Rhizosolenia, Chaetoceros, and Nitzschia (Class Bacillariophyceae), Gymnodinium, Protoperidinium, Alexandrium, and Ceratium (Class Dinophyceae), and Phaeocystis (Class Prymnesiophyte). The highest abundance of potential HABs varied between research stations, Rhizosolenia sp. of 7.6388x104 cells/l at station 1, Leptocylindrus sp. of 5.4504x104 cells/l, Phaeocystis sp. of 4.0x104 cells/l at Station 2. On the other hand, the lowest abundance was Nitzschia sp. of 4.1291x102 cells/l at Station 1, Gymnodinium sp. of 4.1291x102 cells/l at Station 2, and Pseudo Nitzschia sp. of 1.2387x103 cells/l at Station 3. Generally, the ecological condition of the phytoplankton community in Ternate Island Waters has a moderate level of species diversity with fairly even distribution of species and no dominance of certain species.